Technological Capability of Selected Palm Oil Mills in Nigeria - Owolarafe, K.; Ogunsina, B. S.; Obayopo, S. O.; Morakinyo, T. A; Binuyo, G. O.; Okorie, V. O.; Falana, O. B.; Owolabi, I. A.; Badmus, G. A.; Olaoye, I. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
An assessment of the technological capability of some modern palm oil mills in selected states of Nigeria (viz: Edo, Ogun, Ondo and Osun States) for production of special palm oil was carried out in this study. Information regarding the year of establishment of the mills, ownership of the mills, available facilities, production capacity and status of the mills (among others) were collected from the staffs of the mills. It was observed that government-owned mills (Okitipupa and Nigerian Institute for Oil Palm Research with capacities of 24 and 6 tons/hr, respectively) were in dilapidated condition and not functioning due to lack of proper maintenance. The mills had resulted into the utilization of intermediate technologies that can barely produce special palm oil and hence the huge investment in the mills has been wasted. In contrast, privately-owned mills (Okomu, JB and Royal Farm with capacities of 45, 8 and 3 tons/hr, respectively) which were also visited were functional. Two of them (Okomu and JB) were observed to have state of the art technologies for production of special palm oil and adopted well-arranged routine maintenance of the mills’ facilities. The study recommended that the existing public mills should be revived through public-private partnership system while privately-owned small-scale mills can be organized into groups such that they can acquire modern facilities for production of special palm oil. It is also recommended that there should be appropriate linkage between the mills and research institutes for sustainability.